Peningkatan Semangat Literasi, Kreativitas Dengan Bercerita Dan Story Telling - Tria Putri Mustika; Leo Andalas; Dessy Syahfitri; Sapna Sapna; Tengku Dhea Aqilah; Novi Ramadhani; Swelly Via Marsella; Hanny Eka Putri; Irwansyah Ahmad Sinaga; Risma Hoiriah Lubis; Zakarias Sroyer (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
Riau University as a state university that has the duties and functions of implementing the Tri Dharma of Higher Education, namely education and teaching, research, and community service. The form of community service carried out by students is in the form of Real Work Lectures (KUKERTA). KUKERTA is a field learning activity carried out by students that aims to have a positive impact on the community by providing learning in an innovative and creative way, as well as developing potential and knowing the strengths and weaknesses of the local community. This activity is expected to increase student creativity to implement their knowledge in carrying out work programs and provide learning for students in interacting with the community. Real Work Lecture (KUKERTA) is one of the compulsory subjects taken at the University of Riau when entering an odd semester or having fulfilled the credit requirements set by the University of Riau.